Perbedaan Kadar Kolesterol Total Segera Diperiksa Dan Disimpan 7 Hari Suhu 2-8 C Serum Pasien Sindrom Koroner Akut - Adinda Melliza; Subrata Tri Widada; Dhika Juliana Sukmana; Rita Rena Pudyastuti; Sujono Sujono (Puslitbang Sekawan Institute Nusa Tenggara, 2026)
Measurement of cholesterol levels is a vital component of lipid profile testing in clinical laboratories. Ideally, cholesterol measurements should be conducted immediately after serum collection to ensure accurate results. Serum can be stored for up to 7 days at 2-8°C to accommodate additional requests or delays, however storage may influence cholesterol test outcomes. The aim of this study was to identify the differences in cholesterol levels between immediately tested serum and serum stored for 7 days at 2-8°C in acute coronary syndrome patients. This research employed a Pre-Experimental Design (non-design). A total of 45 samples were analyzed through two measurements. The first group was tested immediately after serum collection, and the second group was analyzed after storing the serum for 7 days at 2-8°C. Total cholesterol levels were determined using the CHOD-PAP method and data analysis was performed to identify changes in cholesterol levels. The average cholesterol level of immediately tested samples was 137.6, while for samples stored for 7 days, it was 154.9. Results showed a significant difference in cholesterol levels based on storage duration (p=0.010). There is a measurable difference in cholesterol levels between serum tested immediately and serum stored for 7 days at 2-8°C in patients with acute coronary syndrome.